Implementation of a Web-Based Inventory System for Sales Efficiency in Retail Sector MSMEs in Bandung City - Makalalag, Sukiman; Soegoto, Eddy Soeryanto (Universitas Komputer Indonesia, 2025)
Indonesian Government Takes Bandung’s Retail Stores to Court The shelves should be organized. we’re looking into ways to improve stock monitoring with a web-based. We adopted a Waterfall approach for the construction of this system. When we created the stock tracking website. This study is special since we did not do that. We tried it; we actually tried it out in a shop. The system was tested by them. We wanted to see if the system would actually work well in a real situation. We tested it in. I attempted it. I witnessed what happened. This is basically the definition of black-box testing, right? I used the “Black Box” testing method to see what would happen after just kicking the tires on it. We have just seen the results. The system was working perfectly; all the businesses in Bandung that. The decision to use the web-based inventory system was 100% successful. The main thing is, once we. Our operations improved greatly when we began using it. According to our stock data, transaction timelines dropped by 83%. This new system reduced stock shortages by 90% and was 98% accurate. So, it seems like it helps. More sales and improved performance for business. It’s a fairly suitable solution for smaller and midsized.